Post COVID-19 condition among adults in Malaysia following the Omicron wave: A prospective cohort study. - Peter Seah Keng Tok; Kong Yeow Kang; Sock Wen Ng; Norazida Ab Rahman; Muhammad Aminul Syahmi; Mohan Dass Pathmanathan; Maheshwara Rao Appannan; Kalaiarasu M Peariasamy; Sheamini Sivasampu (PLoS ONE, 2024)
Post COVID-19 condition is an important public health problem as we emerge from the COVID-19 pandemic. In this prospective cohort study, we aimed to determine the prevalence of this condition and assess its associated factors and impact on health-related quality of life in a population setting in Malaysia. Study was conducted from April to June 2022 when the Omicron variant predominated. All individuals testing positive for SARS-CoV-2 infection (RT-PCR, RTK-Ag) were invited for participation. Study questionnaires were delivered via the MySejahtera platform (mobile application). From the total of 44,386 participants who provided responses up to 3-months interval, 1,510 participants (3.4%) fulfilled the post COVID-19 condition criteria. Majority of the affected participants (83.8%, n = 1,265) experienced either cough, fatigue or forgetfulness-the three most common symptoms. Being females, having existing comorbidities, presence of symptoms and requiring hospital admission during the acute illness were associated with higher likelihoods of developing the post COVID-19 condition at 3-months interval. Amongst the 1,510 individuals, one in five had limitations in performing their usual daily activities while at least one in three expressed that their work was affected. Understanding this condition better is essential to guide strategic and responsive plans of action, which may require coordinated multidisciplinary interventions.